Entre linguagem: desconstrução de Jacques Derrida e expansão de campo de Rosalind Krauss (d)nas artes espaciais - Possamai, Edson Rodrigo (My University, 2023)
This research approaches reflections on communication and dialogue through the arts of the body by understanding language in expanded field. With this research, some considerations are made about language, arts of the body and their processes involving creation and fruition as other means of communication and dialogue. Aiming to expose possibilities about reflections on the language permitted by the arts of the body, this study starts from the intersection of Jacques Derrida's notions of deconstruction, trace and event and Rosalind Krauss's concept of expanded field, seeking to perceive the possibility of expansion of the concepts of language present in contemporary artistic manifestations in their processes of creation and fruition. For this purpose, the proposal of spatial arts as art of the body and the possible relations of dialogue between artist, work and spectator was studied. Considering its relevance by the transversality that is necessary for the areas of spatial arts language, this study aims to support the research and creation processes in the arts of the body and in language studies, conducted by the argument space, body and communication. Through the method of bibliographic research of comparative and interpretive analysis, the theoretical foundation is based mainly on the studies of Derrida (1998, 2004, 2007, 2008, 1991, 2001, 2022), Krauss (2008), Salles (2017), Jeudy (2002), Cattani (2010), Rancière (2012) and Santaella (2008). In its corpus, this study raises considerations on language, art and the body, demonstrating the relevance of an understanding about the possibility of language in an expanded field in the relations of creation/fruition of/in the arts of the body, through their presence/absence, among, notations and warnings. [resumo fornecido pelo autor]
Esta dissertação aborda algumas reflexões acerca da comunicação e do diálogo por meio das artes do corpo num entendimento de linguagem em campo expandido. Com esta pesquisa, propõem-se reflexões acerca da linguagem, das artes do corpo e seus processos de criação e fruição como outros meios de comunicação e diálogo. Com o objetivo de expor possibilidades acerca de reflexões sobre a linguagem que as artes do corpo permitem, o estudo parte do cruzamento das noções de Jacques Derrida de desconstrução, rastro e acontecimento e do conceito de campo expandido de Rosalind Krauss, buscando perceber a possibilidade de expansão dos conceitos de linguagem presentes nas manifestações artísticas contemporâneas em seus processos de criação e fruição. Para tanto, estudou-se a proposta de artes espaciais como arte do corpo e as possíveis relações de diálogo entre artista, obra e fruidor. Justificada sua relevância pela transversalidade necessária para as áreas da linguagem e das artes espaciais, tem-se em vista, com este estudo, auxiliar nos processos de pesquisa e criação nas artes do corpo e em estudos em linguagem, orientando-se pelo argumento espaço, corpo e comunicação. Sob o método de uma pesquisa bibliográfica de análise comparativa e interpretativa, a fundamentação teórica baseia-se, principalmente, nos estudos de Derrida (1998, 2004, 2007, 2008, 1991, 2001, 2022), Krauss (2008), Salles (2017), Jeudy (2002), Cattani (2010), Rancière (2012) e Santaella (2008). Em seu corpus, o estudo expõe reflexões acerca da linguagem, da arte e do corpo, demonstrando a relevância de um entendimento acerca da possibilidade da linguagem em campo expandido nas relações de criação/fruição das/nas artes do corpo, por meio de sua presença/ausência, do entre, de notações e advertências. [resumo fornecido pelo autor]
Keywords: Linguagem corporal; Comunicação; Diálogo; Derrida, Jacques, 1930-2004; Krauss, Rosalind Epstein, 1940-; Body language; Communication; Dialogue